(untitled) (Stamford Journal of Microbiology, 2020)
Vaccination against highly pathogenic avian influenza virus (HPAIV) of subtype H5N1 is one of the possible means to protect chickens against its outbreak in endemic countries. Early vaccination of layer birds with recombinant vector vaccine based on turkey herpesvirus expressing H5 gene (rHVT-H5) provides longer protection while inactivated vaccine Re-6 needs multiple booster doses to achieve continuous antibody titer. Therefore, this study was carried out to offer a vaccination program using live rHVT-H5 and inactivated Re-6 vaccines in field condition. For this trial, five ISA brown commercial layer chicken farms were raised with 500 birds per farm. Two licensed vaccines- rHVT-H5 and Re-6 in Bangladesh were used for this trial where birds in farms 1 and 2 were administered only rHVT-H5 vaccine at one-day-old, and farms 3 and 4 rHVT-H5 vaccine at one-day-old then boosted with Re-6 vaccine at 25 weeks of age. Farm 5 was not vaccinated and functioned as control. Blood samples were randomly collected from 20 birds in each farm at 3-week interval from 2 weeks old till 65 weeks and harvested serum analyzed by haemagglutination inhibition (HI) test for antibodies against HPAIV H5N1. The titer of haemagglutination inhibiting antibodies against AIV H5N1 on farms 3 and 4 was considerably high and remained up to 65 weeks. However, in farm 1 and 2 there was decline in antibody titer after 56 weeks of age. This study demonstrated that the combined use of rHVT-H5 vaccine at one-day-old and Re-6 at 25 weeks of age enhanced a longer lasting protective antibody against circulating HPAIV H5N1 in commercial layer chickens in Bangladesh. Stamford Journal of Microbiology, Vol.10 (1) 2020: 9-11